A Route Well Travelled. The archaeology of the A14 Huntingdon to Cambridge Road Improvement Scheme - Emma West; Claire Christie; Debora Moretti; Owain Scholma-Mason; Alex Smith (Internet Archaeology)
The National Highways A14 Road Improvement Scheme between Cambridge and Huntingdon in Cambridgeshire gave rise to one of the largest commercial archaeological projects ever undertaken in the UK. Excavations over 232ha took place between 2016 and 2022 from the Great Ouse Valley near Huntingdon in the west to the higher clay lands towards Cambridge in the east. They involved a huge collaborative team led by MOLA-Headland Infrastructure and revealed groundbreaking archaeology of all periods, from mammoths to medieval villages. This monograph is intended to act as gateway to the project's findings, synthesizing the results in a series of period-based chapters and linking back to the detailed site and specialist reports and the entire digital archive of the project hosted by the Archaeology Data Service.